Perancangan Bisnis Proses Persediaan Bahan Baku Dodol pada Gudang: (Studi Kasus: PT. X) - Rahmawati, Dewi; Mauluddin, Yusuf; Maida, Tisah (Institut Teknologi Garut, 2024)
Garut Regency has unique characteristics, one of which is the famous souvenir industry. One of the culinary industries typical of Garut is Dodol Garut. Dodol Factory PT. Dr. However, there are still several manual processes in factory operations that have the potential to be developed into a more efficient system. This difficulty arises because inventory management is still done manually, resulting in a stock recording process that is not optimal and takes a long time because errors often occur in data management. The aim of this research is to develop business processes and information systems that can be used in managing dodol raw material warehousing. The business process method uses the FEFO (First Expired First Out) goods entry and exit system, as well as an ABC Classification-based raw material procurement decision making system. Mock-ups are used in prototype modeling to obtain the right system design. UML (Unified Modeling Language) diagrams are used to build information systems. This research resulted in a business process design and mock-up of a raw material warehouse information system. The results of the analysis are safety stock output, economic order quantity, and reorder point, where the system can calculate raw material stock and ABC classification so that it can prioritize raw material procurement.